Parham, J. (Ed.) (2021). The Cambridge Companion to Literature and the Anthropocene. - Interdonato, Roberto (Journal of Ecohumanism, 2023)
Parham, J. (Ed.) (2021). The Cambridge Companion to Literature and the Anthropocene. Cambridge University Press.